SUPPRESSOR CELLS – THE BASIS OF IMMUNOPATHOGENESIS AUTOIMMUNE DISEASES - V. A. Kozlov (SPb RAACI, 2016)
The issues of immune pathogenesis in autoimmune pathology are discussed in this review. The main attention is drawn to potential pathogenetic role of various suppressor cell populations, including T-regulatory cells, mesenchymal stem cells, myeloid lineage-derived suppressors. Homeostatic lymphocyte proliferation is considered to be of great importance for pathogenesis of autoimmune disorders. Recent data from literature suggest that the autoimmune diseases are characterized by reduced activity of the mentioned suppressor cell populations, thus being a possible prerequisite for development of autoaggressive clones of cytotoxic lymphocytes, increased synthesis of autoantibodies leading to evolving autoimmune pathology. It should be, however, noted, that all these processes are accompanied by changes in the immune system induced by homeostatic proliferation of lymphoid cells.